你只需要扩展一点弗莱姆的答案:
using System;
using System.Linq.Expressions;
using NUnit.Framework;
public class Person
{
public string FirstName { get; set; }
public string LastName { get; set; }
}
public static class ExpressionBuilder
{
public static Expression<Func<TClass, TProperty>> Build<TClass, TProperty>(string fieldName)
{
var param = Expression.Parameter(typeof(TClass));
var field = Expression.PropertyOrField(param, fieldName);
return Expression.Lambda<Func<TClass, TProperty>>(field, param);
}
}
[TestFixture]
public class Test
{
[Test]
public void TestExpressionBuilder()
{
var person = new Person { FirstName = "firstName", LastName = "lastName" };
var expression = ExpressionBuilder.Build<Person, string>("FirstName");
var firstName = expression.Compile()(person);
Assert.That(firstName, Is.EqualTo(person.FirstName));
}
}